Profane illumination : Walter Benjamin and the Paris of surrealist revolution - Cohen, Margaret, 1958- (Berkeley : University of California Press, 1993)
Margaret Cohen's encounter with Walter Benjamin, one of the twentieth century's most influential cultural and literary critics, has produced a radically new reading of surrealist thought and practice. Cohen analyzes the links between Breton's surrealist fusion of psychoanalysis and Marxism and Benjamin's post-Enlightenment challenge to Marxist theory. She argues that Breton's surrealist Marxism played a formative role in shaping postwar French intellectual life and is of continued relevance to the contemporary intellectual scene.
Based on the author's thesis--Yale University.
Includes bibliographical references (pages 261-268) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Benjamin, Walter, -- 1892-1940.; Benjamin, Walter, -- 1892-1940; Philosophy, Marxist; Surrealism; Paris (France) -- Intellectual life -- 20th century; Philosophy, German -- 20th century; Philosophie marxiste; Surréalisme.; Paris (France) -- Vie intellectuelle -- 20e siècle.; Philosophie allemande -- 20e siècle.; Surrealist; LITERARY CRITICISM -- European -- German; Intellectual life; Philosophy, German; Philosophy, Marxist; Surrealism; France -- Paris; 1900-1999